Maximal sprint power in road cyclists after variable and nonvariable high-intensity exercise - Menaspà, P.; Martin, D. T.; Victor, J.; Abbiss, C. R. (The Journal of Strength and Conditioning Research, 2015)
This study compared the sprint performance of professional cyclists after 10 minutes of variable (VAR) or nonvariable (N-VAR) high-intensity cycling with sprint performance in a rested state. Ten internationally competitive male cyclists (mean ± SD: age, 20.1 ± 1.3 years; stature, 1.81 ± 0.07 m; body weight, 69.5 ± 4.9 kg; and VO2peak, 72.5 ± 4.4 ml/kg/min) performed a 12-second maximal sprint in 3 conditions: (a) a rested state, (b) after 10 minutes of N-VAR cycling, and (c) after 10 minutes of VAR cycling. The intensity during the 10-minute efforts gradually increased to replicate power output observed in the final section of cycling road races. During the VAR cycling, participants performed short (2 seconds) accelerations at 80% of their sprint peak power, every 30 seconds. Average power output, cadence, and maximal heart rate (HR) during the 10-minute efforts were similar between conditions (5.3 ± 0.2 W/kg, 102 ± 1 rpm, and 93 ± 3% HRmax). Postexercise blood lactate concentration and sessional perceived exertion were also similar (8.3 ± 1.6 mmol/L, 15.4 ± 1.3 [6-20 scale]). Peak and average power output and cadence during the subsequent maximal sprint were not different between the 3 experimental conditions (p > 0.05). In conclusion, this study showed that neither the VAR nor the N-VAR 10-minute efforts ridden in this study impaired sprint performance in elite competitive cyclists.